Обоснование необходимости разработки стартового устройства геохода; Технологии и материалы; № 1 - Коперчук А. В. Александр Викторович; Казанцев А. А. Антон Александрович; Бегляков В. Ю. Вячеслав Юрьевич; Филонов В. В. (2015, 2015)
Заглавие с экрана